Impact of plant-based nanoparticles synthesized from Carica papaya and Bryophyllum pinnatum against selected microorganisms - Francis Aibuedefe IGIEBOR; Favour Chinaza MICHAEL; Ochoyama HARUNA; Beckley IKHAJIAGBE (Studia Universitatis Babeș-Bolyai. Biologia, 2024)
Plant-based nanoparticles offer sustainable, eco-friendly alternatives to conventional methods, promising antibacterial properties in the face of antibiotic resistance and addressing global health concerns. Five urine and stool samples were collected from the Benin Medical Centre in Benin City, Edo State, and sent to the Wellspring University Research Laboratory for microbiological analysis. Carica papaya and Bryophyllum pinnatum were used for fresh utilization by washing, weighing, and crushing their leaves, then mixing them with distilled water and heating at 85 °C and 60 °C for 60 minutes. Silver and copper nanoparticles (AgNPs and CuNPs) were synthesized using standard procedures. The NPs were preliminary validated by visual detection of color changes and characterized using a UV-visible spectrophotometer at 300 nm and Fourier transform infrared. The in vitro antimicrobial activity of plant-mediated NPs was investigated using five isolates: S. aureus, B. alvei, H. pylori, P. aeruginosa, and E. coli. The in vitro antimicrobial activity of plant-mediated NPs was investigated using five clinical strains displaying multiple resistance to antibiotics: S. aureus, B. alvei, H. pylori, P. aeruginosa, and E. coli. The agar-well diffusion method showed inhibition of the isolates by plant-mediated NPs but no inhibition by the plant extract alone. The study indicates that plant-mediated NPs exhibit promising antimicrobial activity, promoting sustainability and eco-friendliness, but further research is needed to assess their safety and efficacy in clinical settings.